DYNAMICS OF BEMISIA TABACI ON POTATO CULTIVARS GROWN UNDER ORGANIC AND INORGANIC CONDITIONS IN NORTH-WESTERN INDIA - Bhatanagar, Anuj (Potato Journal, 2021)
Field trials were conducted to assess the incidence of whitefly, Bemisia tabaci (Gennadius) on ten promising potato cultivars grown under organic and inorganic unprotected conditions in North-Western India for three consecutive years 2016-17, 2017-18 and 2018-19, respectively. Data on population build-up of whitefly on potato cultivars (K. Mohan, K. Garima, K. Ganga, K. Khyati, K. Anand, K. Bahar, K. Pukhraj, K. Sindhuri, K.Chipson-3 and K.Chipson-1) revealed that whitefly incidence was higher on potato cultivars grown under inorganic conditions as compared to organic soil amendments. Maximum mean incidence of whitefly was recorded on K. Pukhraj followed by K. Khyati, K. Anand, K. Garima, and K. Ganga with minimum incidence on K. Sindhuri, K.Chipson-3 and K.Chipson-1, K. Mohan and K. Bahar under inorganic as well as organic soil amendments. K. Mohan was recorded maximum tuber yield 51.4, 47.6 and 38.5 t/ ha under inorganic conditions while it was 28.3, 30.3 and 20.6 t/ha comparatively less tuber yield of K. Mohan in organic soil amendment during the years 2016-17, 2017-18 and 2018-19, respectively. High yielder potato cultivar, K. Mohan was performed well with maximum tuber yield under both organic and inorganic conditions with least incidence of whitefly during three consecutive years.